Child discipline education concept in the perspective of Bukhari Hadeeths and its relevance to the thought of Muhammad Iqbal - Andriana, Nesia; Mujahidin, Endin; Subagiya, Bahrum (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
Self-discipline is one of the fundamental characters in education. The elementary school age is a critical age in child education. This research aims to extract the educational concept within Bukhari’s hadeeths as well as analyzing their relevance to the Muhammad Iqbal’s thought. This research employs a qualitative method through quasi experiment and historical literature review. The results showed a significant correlation between the concept of self-discipline education in Bukhari's hadith and the concept of education in Iqbal's thought. The purpose of education according to Iqbal is to form a cognitively, spiritually, and dynamically integrated human being to become the khalifah of Allah on earth. This is in line with the purpose of discipline education in Bukhari's hadith. Educational methods such as exemplary, discussion, appreciation, sanctions, and habituation in Iqbal's thought are also found in Bukhari's hadith. Educational evaluation emphasizes the importance of loyalty to Allah and His Messenger, by upholding justice regardless of time and place. This study concludes that there is a significant relevance between children's discipline education in Bukhari's hadith and Muhammad Iqbal's thought. Abstrak Kedisiplinan adalah salah satu karakter mendasar dalam pendidikan. Usia sekolah dasar adalah usia kritis dalam pendidikan anak. Penelitian ini bertujuan untuk mengekstrak konsep pendidikan yang terkandung dalam hadits-hadits Bukhari serta menganalisa relevansinya dengan pemikiran Muhammad Iqbal. Metode yang digunakan adalah kualitatif dengan kuasi eksperimen serta studi pustaka dan sejarah. Hasil penelitian menunjukkan adanya korelasi signifikan antara konsep pendidikan disiplin diri anak dalam hadits Bukhari dan konsep pendidikan dalam pemikiran Iqbal. Tujuan pendidikan menurut Iqbal adalah membentuk manusia yang terintegrasi secara kognitif, spiritual, dan dinamis untuk menjadi khalifah Allah di bumi. Ini sejalan dengan tujuan pendidikan disiplin dalam hadits Bukhari. Metode pendidikan seperti keteladanan, diskusi, apresiasi, sanksi, dan pembiasaan dalam pemikiran Iqbal juga ditemukan dalam hadits Bukhari. Evaluasi pendidikan menekankan pentingnya loyalitas kepada Allah dan Rasul-Nya, dengan menegakkan keadilan tanpa memandang waktu dan tempat. Penelitian ini menyimpulkan bahwa ada relevansi signifikan antara pendidikan disiplin anak dalam hadits Bukhari dan pemikiran Muhammad Iqbal.